2010
DOI: 10.1002/elps.201000188
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial peptide ligand library plasma treatment: Advantages for accessing low‐abundance proteins

Abstract: Depletion of major blood proteins is one of the most promising approaches to accessing low-abundance biomarkers. This study compared the use of combinatorial peptide ligand library (CPLL) and albumin and immunoglobulins (IgGs) depletion technology for accessing these low-abundance proteins in plasma using 2-DE in an acidic restricted pH range (4-7). Compared with native plasma, both techniques enlarge the visibility of other proteins than albumin and IgG, but there were marked differences in their composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…range of proteins present in plasma makes their analysis challenging, because high-abundance proteins tend to mask or interfere with the detection of proteins components present in small amounts [12]. Thus, depletion of these high-abundance plasma proteins prior to further analysis is a logical preprocessing step.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…range of proteins present in plasma makes their analysis challenging, because high-abundance proteins tend to mask or interfere with the detection of proteins components present in small amounts [12]. Thus, depletion of these high-abundance plasma proteins prior to further analysis is a logical preprocessing step.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ProteoMiner enrichment kit (Bio-Rad, USA) utilizes a combinatorial library of hexapeptides rather than immunodepletion, minimizing the dependence on available antibodies and preventing the codepletion of low-abundance proteins [12]. In this study, we processed plasma samples with ProteoMiner enrichment kit (Bio-Rad, USA)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other investigators have reported similar results. Beseme et al [32] and Sihlbom et al [18] compared the use of CPLL with albumin and IgG immunodepletion. These investigators detected an additional 30%-60% of protein spots on 2-D gels with CPLL.…”
Section: Effectiveness Of Biomarker Discovery Protocolmentioning
confidence: 99%
“…The results are as follows: eluant 4 M urea11% CHAPS seems to elute not more than 20% of the captured species, the remaining 80% appearing only in the second eluate. In the case of 4 M urea, 1% CHAPS and 5% acetic acid, the elution power was augmented by a factor of three, up to 60%, whereas in the last case (8 M urea, 1% CHAPS and 5% acetic acid) the eluate represents about 80% (4 Â of eluant (i)) of the total [15] (i) 4 M urea, 1% CHAPS, 5% acetic acid; 320 proteins in PM; 332 immuno-depletion (ii) 6 M guanidine HCl, pH 6.0 [17] 4 M urea, 1% CHAPS, 5% acetic acid Many more SELDI peaks than control [18] (i) 8 M urea, 2% CHAPS, 5% acetic acid Identical spots in 2D maps (ii) 7 M urea, 2 M thiourea, 4% CHAPS, 40 mM Tris [19] 4 M urea, 1% CHAPS, 5% acetic acid Control: 157 spots; PM treated: 557 spots, IPGs pH 4-7 [20] 8 M urea, 2% CHAPS, 5% acetic acid Control: 48 peaks; PM-treated: 136 Peaks in SELDI [13] 4 M urea, 1% CHAPS Only high abundance proteins 1 mg to 40 mg/mL [21] 100 mM Tris-HCL pH 6.8, 4% SDS, 10% 2-ME, boil Untreated: 251 proteins; PM-treated: 693 proteins; saliva [14] 33.3% 2-propanol, 16.7% ACN, 0.1% TFA) 108 proteins unique to PM; 100 proteins unique to IgY; 404 total proteins; sera [23] (i) 8 M urea, 2% CHAPS, 5% acetic acid; Control: 211 proteins ; CPLL-treated: 512 a)…”
mentioning
confidence: 99%
“…It turns out that there are essentially four main elution cocktails, which are listed here: (i) 4 M urea1 1% CHAPS [13]; (ii) 4 M urea11% CHAPS15% acetic acid [14,15,17,19]; (iii) 8 M urea12% CHAPS15% acetic acid [18,20,23]; and (iv) boiling 4% SDS125 mM DTT [21][22][23]. Briefly, the experimental protocol is as follows: 1 mL of serum is incubated for 3 h, on a rotating platform, with 50 mL of CPLL beads.…”
mentioning
confidence: 99%